Preparation method of cobalt-copper bimetallic oxide nanotube array self-supporting electrode with hollow heterostructure
By adopting a hollow heterostructured cobalt copper bimetal oxide nanotube array self-supporting electrode in blood glucose detection, the problem of insufficient stability and sensitivity of existing electrochemical sensors is solved, and glucose detection with high sensitivity and stability is achieved.
Patent Information
- Application Number
- CN202510107325.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-04-22
AI Technical Summary
The existing electrochemical sensors used in blood glucose detection methods have poor stability and sensitivity, which limits their application in diabetes monitoring.
The cobalt-copper bimetal oxide nanotube array self-supporting electrode adopts hollow heterostructure, and the transition metal oxide nanotube array is grown in situ through foam copper to form a three-dimensional structure with good conductivity and porous properties, improving electrochemical activity and sensitivity.
It achieves high sensitivity, selectivity and stability for glucose detection, can accurately detect glucose in blood, sweat and saliva, and has strong anti-interference.
Smart Images

Figure CN119861125A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a nanotube array self-supporting electrode. Background Art
[0002] Diabetes is a metabolic disease characterized by elevated blood sugar levels, which poses a major threat to human health and causes numerous complications. Therefore, effective monitoring of blood sugar levels is crucial for early detection and timely intervention of diabetic patients. In medical testing, the glucose content in body fluids such as blood, urine, sweat and saliva is mainly used to diagnose diabetes. At present, the mainstream blood sugar detection method on the market is based on glucose oxidase (GO x ) or dehydrogenase-based glucose electrochemical sensors, but their development is limited by the disadvantages of high enzyme cost, poor stability, and complex assembly. In recent years, non-enzymatic glucose electrochemical sensors (NEGS) have been sought after by many scholars in the research of electrochemical glucose detection due to their simple functions, fast response, and extremely high sensitivity. Although the advantages of noble metal (such as Au, Ag, and Pt) electrode materials in electrochemical glucose sensing are well known, the noble metal Cl - Poisoning problems, high prices, and poor sensitivity have hindered its widespread application. Summary of the invention
[0003] The purpose of the present invention is to solve the technical problems of poor stability and poor sensitivity of electrochemical sensors used in existing blood sugar detection methods, and to provide a method for preparing a self-supporting electrode of a hollow heterostructured cobalt-copper bimetallic oxide nanotube array.
[0004] The preparation method of the hollow heterostructured cobalt-copper bimetallic oxide nanotube array self-supporting electrode is as follows:
[0005] 1. Cut the foam copper into 2cm×3cm sheets, and use 1mol / L hydrochloric acid, acetone, deionized water, and ethanol to ultrasonically clean for 10min, respectively, and dry at room temperature for later use;
[0006] 2. Dissolve 2.5 g of sodium hydroxide and 0.71 g of ammonium persulfate in 50 mL of deionized water to obtain solution A;
[0007] 3. Immerse the cleaned copper foam in solution A obtained in step 2 for 15 min, rinse with deionized water and ethanol, dry at room temperature for later use, and obtain Cu(OH)2NTAs / CF;
[0008] 4. Dissolve 2.7 g of urea in 30 mL of deionized water to obtain solution B;
[0009] 5. Transfer solution B to a 80 mL Teflon-lined stainless steel autoclave, and immerse Cu(OH)2NTAs / CF in solution B. The hydrothermal reaction time is 2 h. Then rinse with deionized water and ethanol, and dry at room temperature for use to obtain a Cu(OH)2NTAs / CF precursor.
[0010] 6. Place the precursor in a tube furnace, heat it to 350°C at a heating rate of 2°C / min, react for 2 hours at an annealing temperature of 350°C, cool it to room temperature, wash the product with deionized water, and dry it to obtain a hollow heterostructured cobalt-copper bimetallic oxide nanotube array self-supporting electrode CuO x NTAs / CF 。
[0011] The preparation method of the hollow heterostructured cobalt-copper bimetallic oxide nanotube array self-supporting electrode is as follows:
[0012] 1. Cut the foam copper into 2cm×3cm sheets, and use 1mol / L hydrochloric acid, acetone, deionized water, and ethanol to ultrasonically clean for 10min, respectively, and dry at room temperature for later use;
[0013] 2. Dissolve 2.5 g of sodium hydroxide and 0.71 g of ammonium persulfate in 50 mL of deionized water to obtain solution A;
[0014] 3. Immerse the cleaned copper foam in solution A obtained in step 2 for 15 min, rinse with deionized water and ethanol, dry at room temperature for later use, and obtain Cu(OH)2NTAs / CF;
[0015] 4. Dissolve 2.7 g of urea and 0.873 g of cobalt nitrate hexahydrate in 30 mL of deionized water to obtain solution B;
[0016] 5. Transfer solution B to an 80 mL Teflon-lined stainless steel autoclave and immerse Cu(OH)2NTAs / CF in solution B. The hydrothermal reaction time is 2 h. Then rinse with deionized water and ethanol and dry at room temperature for use. Cu(OH)2NTAs / CF is obtained. 2@ CoCHNTAs / CF 0.1 Precursor;
[0017] 6. Place the precursor in a tube furnace, heat it to 350°C at a heating rate of 2°C / min, react for 2 hours at an annealing temperature of 350°C, cool it to room temperature, wash the product with deionized water, and dry it to obtain a hollow heterostructured cobalt-copper bimetallic oxide nanotube array self-supporting electrode CuO x @Co3O4NTAs / CF 0.1。
[0018] The preparation method of the hollow heterostructured cobalt-copper bimetallic oxide nanotube array self-supporting electrode is as follows:
[0019] 1. Cut the foam copper into 2cm×3cm sheets, and use 1mol / L hydrochloric acid, acetone, deionized water, and ethanol to ultrasonically clean for 10min, respectively, and dry at room temperature for later use;
[0020] 2. Dissolve 2.5 g of sodium hydroxide and 0.71 g of ammonium persulfate in 50 mL of deionized water to obtain solution A;
[0021] 3. Immerse the cleaned copper foam in solution A obtained in step 2 for 15 min, rinse with deionized water and ethanol, dry at room temperature for later use, and obtain Cu(OH)2NTAs / CF;
[0022] 4. Dissolve 2.7 g of urea and 1.746 g of cobalt nitrate hexahydrate in 30 mL of deionized water to obtain solution B;
[0023] 5. Transfer solution B to an 80 mL Teflon-lined stainless steel autoclave and immerse Cu(OH)2NTAs / CF in solution B. The hydrothermal reaction time is 2 h. Then rinse with deionized water and ethanol and dry at room temperature for use. Cu(OH)2NTAs / CF is obtained. 2@ CoCHNTAs / CF 0. Precursor;
[0024] 6. Place the precursor in a tube furnace, heat it to 350°C at a heating rate of 2°C / min, react for 2 hours at an annealing temperature of 350°C, cool it to room temperature, wash the product with deionized water, and dry it to obtain a hollow heterostructured cobalt-copper bimetallic oxide nanotube array self-supporting electrode CuO x @Co3O4 NTAs / CF 0.2。
[0025] The preparation method of the hollow heterostructured cobalt-copper bimetallic oxide nanotube array self-supporting electrode is as follows:
[0026] 1. Cut the foam copper into 2cm×3cm sheets, and use 1mol / L hydrochloric acid, acetone, deionized water, and ethanol to ultrasonically clean for 10min, respectively, and dry at room temperature for later use;
[0027] 2. Dissolve 2.5 g of sodium hydroxide and 0.71 g of ammonium persulfate in 50 mL of deionized water to obtain solution A;
[0028] 3. Immerse the cleaned copper foam in solution A obtained in step 2 for 15 min, rinse with deionized water and ethanol, dry at room temperature for later use, and obtain Cu(OH)2NTAs / CF;
[0029] 4. Dissolve 2.7 g urea and 2.619 g cobalt nitrate hexahydrate in 30 mL of deionized water to obtain solution B;
[0030] 5. Transfer solution B to an 80 mL Teflon-lined stainless steel autoclave and immerse Cu(OH)2NTAs / CF in solution B. The hydrothermal reaction time is 2 h. Then rinse with deionized water and ethanol and dry at room temperature for use. Cu(OH)2NTAs / CF is obtained. 2@ CoCH NTAs / CF 0.3 Precursor;
[0031] 6. Place the precursor in a tube furnace, heat it to 350°C at a heating rate of 2°C / min, react for 2 hours at an annealing temperature of 350°C, cool it to room temperature, wash the product with deionized water, and dry it to obtain a hollow heterostructured cobalt-copper bimetallic oxide nanotube array self-supporting electrode CuO x @Co3O4 NTAs / CF 0.3。
[0032] The high sensitivity, selectivity and stability of Co and Cu transition metal-based NEGS electrodes for glucose detection depend on the careful design of the microstructure and chemical composition of transition metal-based electrode materials. In situ growth of transition metal oxide nanotube arrays on metal foam (copper foam) has good conductivity, porous three-dimensional structure, more active sites and electrocatalytic activity. Nanotube-shaped transition metal oxides can form a good heterogeneous structure, which has better sensitivity, linear range and long-term stability in glucose detection.
[0033] The hollow heterostructured cobalt-copper bimetallic oxide nanotube array self-supporting electrode prepared by this method has the following advantages:
[0034] (1) Large electrochemical active area and bimetallic oxide heterostructure enable high charge transfer efficiency;
[0035] (2) abundant and well-distributed active sites and fast diffusion pathways for glucose and electrolytes;
[0036] (3) It can accurately detect glucose in blood, sweat and saliva and has strong anti-interference ability. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 Schematic diagram of the preparation method of the hollow heterostructured cobalt-copper bimetallic oxide nanotube array self-supporting electrode;
[0038] Figure 2 It is a hollow heterostructured cobalt-copper bimetallic oxide nanotube array self-supporting electrode CuO x@Co3O4NTAs / CF 0.2 Scanning electron microscope image of
[0039] Figure 3 It is a hollow heterostructured cobalt-copper bimetallic oxide nanotube array self-supporting electrode CuO x @Co3O4NTAs / CF 0.2 it curve graph for glucose;
[0040] Figure 4 It is a hollow heterostructured cobalt-copper bimetallic oxide nanotube array self-supporting electrode CuO x NTAs / CF linear fitting curve;
[0041] Figure 5 It is a hollow heterostructured cobalt-copper bimetallic oxide nanotube array self-supporting electrode CuO x @Co3O4NTAs / CF 0.1 Linear fitting curve;
[0042] Figure 6 It is a hollow heterostructured cobalt-copper bimetallic oxide nanotube array self-supporting electrode CuO x @Co3O4NTAs / CF 0.2 Linear fitting curve;
[0043] Figure 7 It is a hollow heterostructured cobalt-copper bimetallic oxide nanotube array self-supporting electrode CuO x @Co3O4NTAs / CF 0.3 Linear fitting curve. DETAILED DESCRIPTION
[0044] The technical solution of the present invention is not limited to the specific implementation modes listed below, but also includes any combination of the specific implementation modes.
[0045] Specific implementation method 1: The preparation method of the hollow heterostructured cobalt-copper bimetallic oxide nanotube array self-supporting electrode of this implementation method is as follows:
[0046] 1. Cut the foam copper into 2cm×3cm sheets, and use 1mol / L hydrochloric acid, acetone, deionized water, and ethanol to ultrasonically clean for 10min, respectively, and dry at room temperature for later use;
[0047] 2. Dissolve 2.5 g of sodium hydroxide and 0.71 g of ammonium persulfate in 50 mL of deionized water to obtain solution A;
[0048] 3. Immerse the cleaned copper foam in solution A obtained in step 2 for 15 min, rinse with deionized water and ethanol, dry at room temperature for later use, and obtain Cu(OH)2NTAs / CF;
[0049] 4. Dissolve 2.7 g of urea in 30 mL of deionized water to obtain solution B;
[0050] 5. Transfer solution B to a 80 mL Teflon-lined stainless steel autoclave, and immerse Cu(OH)2NTAs / CF in solution B. The hydrothermal reaction time is 2 h. Then rinse with deionized water and ethanol, and dry at room temperature for use to obtain a Cu(OH)2NTAs / CF precursor.
[0051] 6. Place the precursor in a tube furnace, heat it to 350°C at a heating rate of 2°C / min, react for 2 hours at an annealing temperature of 350°C, cool it to room temperature, wash the product with deionized water, and dry it to obtain a hollow heterostructured cobalt-copper bimetallic oxide nanotube array self-supporting electrode CuO x NTAs / CF 。
[0052] Specific embodiment 2: The method for preparing the self-supporting electrode of the hollow heterostructured cobalt-copper bimetallic oxide nanotube array in this embodiment is as follows:
[0053] 1. Cut the foam copper into 2cm×3cm sheets, and use 1mol / L hydrochloric acid, acetone, deionized water, and ethanol to ultrasonically clean for 10min, respectively, and dry at room temperature for later use;
[0054] 2. Dissolve 2.5 g of sodium hydroxide and 0.71 g of ammonium persulfate in 50 mL of deionized water to obtain solution A;
[0055] 3. Immerse the cleaned copper foam in solution A obtained in step 2 for 15 min, rinse with deionized water and ethanol, dry at room temperature for later use, and obtain Cu(OH)2NTAs / CF;
[0056] 4. Dissolve 2.7 g of urea and 0.873 g of cobalt nitrate hexahydrate in 30 mL of deionized water to obtain solution B;
[0057] 5. Transfer solution B to an 80 mL Teflon-lined stainless steel autoclave and immerse Cu(OH)2NTAs / CF in solution B. The hydrothermal reaction time is 2 h. Then rinse with deionized water and ethanol and dry at room temperature for use. Cu(OH)2NTAs / CF is obtained. 2@ CoCHNTAs / CF 0.1 Precursor;
[0058] 6. Place the precursor in a tube furnace, heat it to 350°C at a heating rate of 2°C / min, react for 2 hours at an annealing temperature of 350°C, cool it to room temperature, wash the product with deionized water, and dry it to obtain a hollow heterostructured cobalt-copper bimetallic oxide nanotube array self-supporting electrode CuO x @Co3O4NTAs / CF 0.1。
[0059] Specific implementation method 3: The preparation method of the hollow heterostructured cobalt-copper bimetallic oxide nanotube array self-supporting electrode of this implementation method is as follows:
[0060] 1. Cut the foam copper into 2cm×3cm sheets, and use 1mol / L hydrochloric acid, acetone, deionized water, and ethanol to ultrasonically clean for 10min, respectively, and dry at room temperature for later use;
[0061] 2. Dissolve 2.5 g of sodium hydroxide and 0.71 g of ammonium persulfate in 50 mL of deionized water to obtain solution A;
[0062] 3. Immerse the cleaned copper foam in solution A obtained in step 2 for 15 min, rinse with deionized water and ethanol, dry at room temperature for later use, and obtain Cu(OH)2NTAs / CF;
[0063] 4. Dissolve 2.7 g of urea and 1.746 g of cobalt nitrate hexahydrate in 30 mL of deionized water to obtain solution B;
[0064] 5. Transfer solution B to an 80 mL Teflon-lined stainless steel autoclave and immerse Cu(OH)2NTAs / CF in solution B. The hydrothermal reaction time is 2 h. Then rinse with deionized water and ethanol and dry at room temperature for use. Cu(OH)2NTAs / CF is obtained. 2@ CoCHNTAs / CF 0. Precursor;
[0065] 6. Place the precursor in a tube furnace, heat it to 350°C at a heating rate of 2°C / min, react for 2 hours at an annealing temperature of 350°C, cool it to room temperature, wash the product with deionized water, and dry it to obtain a hollow heterostructured cobalt-copper bimetallic oxide nanotube array self-supporting electrode CuO x @Co3O4 NTAs / CF 0.2。
[0066] Specific embodiment 4: The method for preparing the self-supporting electrode of the hollow heterostructured cobalt-copper bimetallic oxide nanotube array in this embodiment is as follows:
[0067] 1. Cut the foam copper into 2cm×3cm sheets, and use 1mol / L hydrochloric acid, acetone, deionized water, and ethanol to ultrasonically clean for 10min, respectively, and dry at room temperature for later use;
[0068] 2. Dissolve 2.5 g of sodium hydroxide and 0.71 g of ammonium persulfate in 50 mL of deionized water to obtain solution A;
[0069] 3. Immerse the cleaned copper foam in solution A obtained in step 2 for 15 min, rinse with deionized water and ethanol, dry at room temperature for later use, and obtain Cu(OH)2NTAs / CF;
[0070] 4. Dissolve 2.7 g urea and 2.619 g cobalt nitrate hexahydrate in 30 mL of deionized water to obtain solution B;
[0071] 5. Transfer solution B to an 80 mL Teflon-lined stainless steel autoclave and immerse Cu(OH)2NTAs / CF in solution B. The hydrothermal reaction time is 2 h. Then rinse with deionized water and ethanol and dry at room temperature for use. Cu(OH)2NTAs / CF is obtained. 2@ CoCH NTAs / CF 0.3 Precursor;
[0072] 6. Place the precursor in a tube furnace, heat it to 350°C at a heating rate of 2°C / min, react for 2 hours at an annealing temperature of 350°C, cool it to room temperature, wash the product with deionized water, and dry it to obtain a hollow heterostructured cobalt-copper bimetallic oxide nanotube array self-supporting electrode CuO x @Co3O4 NTAs / CF 0.3。
[0073] The following experiments were used to verify the effect of the present invention:
[0074] Experiment 1:
[0075] The performance of the self-supporting electrode of the cobalt-copper bimetallic oxide nanotube array with hollow heterostructure prepared in the specific embodiments 1 to 4 was tested using the three-electrode system of Shanghai Chenhua CHI660D electrochemical workstation. The prepared self-supporting electrode was used as the working electrode, the platinum wire electrode was used as the counter electrode, the saturated calomel electrode was used as the reference electrode, and the NaOH solution with a concentration of 0.1 mol / L was used as the electrolyte. The chronoamperometry was used to record the change of current density after continuous addition of different concentrations of glucose under the voltage condition of +0.45 V, and the current time curve ( Figure 3 )
[0076] The linear fitting images of the cobalt-copper bimetallic oxide nanotube array self-supporting electrodes with different hollow heterostructures and the equation of glucose concentration on the response current density are shown in Figure 2. Figure 4-Figure 7As shown. The glucose concentration range is between 10μM-527μM, and the sensitivities of different electrodes are 17091.46, 18833.86, 23347.4 and 20136.64μA mM -1 cm -2 The sensitivity of glucose concentration ranged from 527 μM to 939 mM was 8173.91 μA mM -1 cm -2 、7880.86μAmM -1 cm -2 、8834.17μAmM -1 cm -2 、8448.96μA mM -1 cm -2 .
[0077] According to the results, it can be concluded that CuO x @Co3O4 NTAs / CF 0.2 The performance of the electrode was the best, and the sensitivity, detection limit and linear range of the electrode were calculated to be 23347.4μAmM respectively. -1 cm -2 , 0.56μM and 10-939μM; using CuO x @Co3O4NTAs / CF 0.2 The electrode was tested for spiked recovery of human serum, saliva, and sweat. The results are shown in Table 1. The prepared hollow heterostructured cobalt-copper bimetallic oxide nanotube array self-supporting electrode has a high recovery rate for glucose detection in sweat, saliva, and human serum.
[0078] Table 1
[0079]
Claims
1. A method for preparing a self-supporting electrode of a hollow heterostructured cobalt-copper bimetallic oxide nanotube array, characterized in that The method for preparing the hollow heterostructured cobalt-copper bimetallic oxide nanotube array self-supporting electrode is as follows:
1. Clean the copper foam with 1 mol / L hydrochloric acid, acetone, deionized water, and ethanol for 10 min respectively, and dry it at room temperature for later use; 2. Dissolve 2.5 g of sodium hydroxide and 0.71 g of ammonium persulfate in 50 mL of deionized water to obtain solution A; 3. Immerse the cleaned copper foam in solution A obtained in step 2 for 15 min, rinse with deionized water and ethanol, dry at room temperature for later use, and obtain Cu(OH)2NTAs / CF; 4. Dissolve 2.7 g of urea in 30 mL of deionized water to obtain solution B; 5. Transfer solution B to a 80 mL Teflon-lined stainless steel autoclave, and immerse Cu(OH)2NTAs / CF in solution B. The hydrothermal reaction time is 2 h. Then rinse with deionized water and ethanol, and dry at room temperature for use to obtain a Cu(OH)2NTAs / CF precursor.
6. Place the precursor in a tube furnace, heat it to 350°C at a heating rate of 2°C / min, react for 2 hours at an annealing temperature of 350°C, cool it to room temperature, wash the product with deionized water, and dry it to obtain a hollow heterostructured cobalt-copper bimetallic oxide nanotube array self-supporting electrode CuO x NTAs / CF 。 2. A method for preparing a self-supporting electrode of a hollow heterostructured cobalt-copper bimetallic oxide nanotube array, characterized in that The method for preparing the hollow heterostructured cobalt-copper bimetallic oxide nanotube array self-supporting electrode is as follows:
1. Clean the copper foam with 1 mol / L hydrochloric acid, acetone, deionized water, and ethanol for 10 min respectively, and dry it at room temperature for later use; 2. Dissolve 2.5 g of sodium hydroxide and 0.71 g of ammonium persulfate in 50 mL of deionized water to obtain solution A; 3. Immerse the cleaned copper foam in solution A obtained in step 2 for 15 min, rinse with deionized water and ethanol, dry at room temperature for later use, and obtain Cu(OH)2NTAs / CF; 4. Dissolve 2.7 g of urea and 0.873 g of cobalt nitrate hexahydrate in 30 mL of deionized water to obtain solution B; 5. Transfer solution B to an 80 mL Teflon-lined stainless steel autoclave and immerse Cu(OH)2NTAs / CF in solution B. The hydrothermal reaction time is 2 h. Then rinse with deionized water and ethanol and dry at room temperature for use. Cu(OH)2NTAs / CF is obtained. 2@ CoCHNTAs / CF 0.1 Precursor; 6. Place the precursor in a tube furnace, heat it to 350°C at a heating rate of 2°C / min, react for 2 hours at an annealing temperature of 350°C, cool it to room temperature, wash the product with deionized water, and dry it to obtain a hollow heterostructured cobalt-copper bimetallic oxide nanotube array self-supporting electrode CuO x @Co3O4NTAs / CF 0.1。 3. A method for preparing a self-supporting electrode of a hollow heterostructured cobalt-copper bimetallic oxide nanotube array, characterized in that The method for preparing the hollow heterostructured cobalt-copper bimetallic oxide nanotube array self-supporting electrode is as follows:
1. Clean the copper foam with 1 mol / L hydrochloric acid, acetone, deionized water, and ethanol for 10 min respectively, and dry it at room temperature for later use; 2. Dissolve 2.5 g of sodium hydroxide and 0.71 g of ammonium persulfate in 50 mL of deionized water to obtain solution A; 3. Immerse the cleaned copper foam in solution A obtained in step 2 for 15 min, rinse with deionized water and ethanol, dry at room temperature for later use, and obtain Cu(OH)2NTAs / CF; 4. Dissolve 2.7 g of urea and 1.746 g of cobalt nitrate hexahydrate in 30 mL of deionized water to obtain solution B; 5. Transfer solution B to an 80 mL Teflon-lined stainless steel autoclave and immerse Cu(OH)2NTAs / CF in solution B. The hydrothermal reaction time is 2 h. Then rinse with deionized water and ethanol and dry at room temperature for use. Cu(OH)2NTAs / CF is obtained. 2@ CoCHNTAs / CF 0.2 Precursor; 6. Place the precursor in a tube furnace, heat it to 350°C at a heating rate of 2°C / min, react for 2 hours at an annealing temperature of 350°C, cool it to room temperature, wash the product with deionized water, and dry it to obtain a hollow heterostructured cobalt-copper bimetallic oxide nanotube array self-supporting electrode CuO x @Co3O4 NTAs / CF 0.2。 4. A method for preparing a self-supporting electrode of a hollow heterostructured cobalt-copper bimetallic oxide nanotube array, characterized in that The method for preparing the hollow heterostructured cobalt-copper bimetallic oxide nanotube array self-supporting electrode is as follows:
1. Clean the copper foam with 1 mol / L hydrochloric acid, acetone, deionized water, and ethanol for 10 min, and dry it at room temperature for later use.
2. Dissolve 2.5 g of sodium hydroxide and 0.71 g of ammonium persulfate in 50 mL of deionized water to obtain solution A; 3. Immerse the cleaned copper foam in solution A obtained in step 2 for 15 min, rinse with deionized water and ethanol, dry at room temperature for later use, and obtain Cu(OH)2NTAs / CF; 4. Dissolve 2.7 g urea and 2.619 g cobalt nitrate hexahydrate in 30 mL of deionized water to obtain solution B; 5. Transfer solution B to an 80 mL Teflon-lined stainless steel autoclave and immerse Cu(OH)2NTAs / CF in solution B. The hydrothermal reaction time is 2 h. Then rinse with deionized water and ethanol and dry at room temperature for use. Cu(OH)2NTAs / CF is obtained. 2@ CoCHNTAs / CF 0.3 Precursor; 6. Place the precursor in a tube furnace, heat it to 350°C at a heating rate of 2°C / min, react for 2 hours at an annealing temperature of 350°C, cool it to room temperature, wash the product with deionized water, and dry it to obtain a hollow heterostructured cobalt-copper bimetallic oxide nanotube array self-supporting electrode CuO x @Co3O4 NTAs / CF 0.3。
Citation Information
Patent Citations
Ultrathin bimetallic molybdate nanosheet coated nanotube heterostructure material and preparation method and application thereof
CN113818041A
Preparation method of platinum-doped copper-cobalt hydroxide array structure
CN113981483A
Preparation method of copper oxide nanowire electrode material and application of copper oxide nanowire electrode material in preparation of glucose sensor
CN114791452A
Self-supporting electrochemical sensing material as well as preparation method and application thereof
CN116413316A
Nitrate sensing electrode based on copper oxide / cerium dioxide heterostructure, preparation method and application thereof
CN118961835A